A cross-sectional investigation of the ophthalmological impact of loiasis in Cameroon, Central Africa. - Joseph Kamgno; Joseph Kamtchum-Tatuene; Linda Esso; Serge Bertrand Eyebe-Eyebe; Giles Kagmeni; Jean Bopda; Jean Tenaguem; Amy Klion; Hugues Nana-Djeunga; Lucienne Bella-Assumpta; Adrian Hopkins (PLoS Neglected Tropical Diseases)
Background Current knowledge of ocular manifestations of loiasis is limited to the transient subconjunctival passage of the adult filaria and anecdotal reports of posterior segment lesions. Therefore, the ocular burden of loiasis is likely underestimated since it has never been systematically assessed at the population level. We aimed to evaluate the relationship of Loa loa microfilaremia and recent eye worm passage with chronic ocular lesions identified through comprehensive ophthalmological assessment in an endemic area. Methodology/principal findings Subjects aged ≥ 15 years, residing in Akonolinga for ≥ 5 years, without filaricidal treatment for ≥3 years, were screened for filariases. After excluding participants with onchocerciasis lesions, a subset of randomly selected participants was assessed by ophthalmologists blinded to blood test results then allocated to four groups defined by microfilarial load (MFL) on calibrated thick blood film: G1 (Loa MFL = 0), G2 (MFL < 8000/mL), G3 (MFL ≥ 8000/mL), G4 (co-infestation with Mansonella MFL > 100/mL). The ophthalmological assessment comprised distance visual acuity, examination of the anterior segment with a slit lamp, and fundoscopy. The primary analysis consisted of univariable comparisons of the frequency of abnormal findings across four groups (G1 - 4) or two groups defined by history of eye worm passage. The secondary analysis consisted of a multivariable logistic regression analysis of the relationship of high Loa MFL (≥8000/mL) with chorioretinitis and eye worm passage with unilateral ametropia, adjusting for confounders. Of 1511 subjects screened, 200 underwent ophthalmological assessment, including 65, 69, 35, and 16 in G1 to 4. History of eye worm passage in the previous year was reported by 121 participants (65.4%). Unilateral ametropia was more prevalent in people with history of eye worm passage in the previous year (26.5% versus 10.9%, p = 0.014). Chorioretinitis was the most frequent posterior segment lesion (n = 11, 6.1%) and was most prevalent in G3 (14.3%). The frequency of chorioretinitis was higher in participants with moderate-to-severe visual impairment (27.3% versus 4.4%, p = 0.002). High Loa MFL was an independent predictor of chorioretinitis (adjusted OR=5.28; p = 0.01). History of eye worm passage in the previous year was independently associated with unilateral ametropia (adjusted OR=3.27, p = 0.0088). Conclusions/significance This study has, for the first time, provided evidence of independent association between history of eye worm passage and unilateral ametropia, and between high Loa MFL and severe chorioretinal lesions. This suggests that loiasis should be classified as a neglected tropical disease.